Off limits: highly sensitive troponin in the general population - Giannitsis, Evangelos; Katus, Hugo (European heart journal, 2016)
Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2016. For permissions please email: journals.permissionsoup.com.This editorial refers to ‘Troponin I and cardiovascular risk prediction in the general population: The BiomarCaRE consortium’†, by S. Blakenberg et al., on page 2428....Risk estimates based on classical risk factors only partially explain the incidence of cardiovascular disease (CVD) in the general population, and risk estimates vary across European populations. The BiomarCaRE project aims to determine the additional value of multiple (new) biomarkers to improve risk estimation of CVD-related events in Europe. In particular, the article by Blankenberg et al.1 in this issue of the journal investigated the value of adding troponin I levels using a highly sensitive assay (Abbott ARCHITECT STAT) to conventional risk factors for prediction of CVD....The investigators evaluated individual level data from 10 prospective population-based studies on a...
Gesehen am 22.03.2018